VEGETATION CHARACTERISTICS AND CARBON STOCKS AFTER EARTHQUAKE IN FOREST FOR SPECIFIC PURPOSE (KHDTK) SENARU - Sitti Latifah; Muhammad Husni Idris; Rato Silamon Firdaus; Niechi Valentino; Eni Hidayati; nuraini nuraini; Tedi Zulia Putra (Pusat Penelitian dan Pengembangan Hutan, 2020)
Kawasan Hutan Dengan Tujuan Khusus (KHDTK) or Forest for Specific Purposes in Senaru is a forest area designated for educational purposes. This study aims to assess ecological changes (i.e., vegetation cover, vegetation structure and diversity, and carbon storage) in KHDTK Senaru during three-time scales, namely in 2013 and in 2018; before and after the earthquake. Data were collected from 30 permanent quadratic plots, systematically distributed in these three different time scales. The vegetation cover resultsshow a decreasing vegetation cover in the dense class but increasing in middle and sparse density classes. Changes in vegetation structure and diversity are noticeable at all regeneration stages, while the carbon storage changes at each time scale. This study indicates that disturbance due to the earthquake has minimal effect on the species diversity than management practices. Therefore, we recommend that the manager or forest users to consider planting more species to increase diversity, improve ecosystemresiliency, prevent damage expansion, and decrease the ecological function of KHDTK Senaru.